On the reactivity of platina-β-diketones: a straightforward synthesis of trans-acetylchlorobis(phosphine)platinum(II) complexes and their reactivity - Albrecht, Christian; Wagner, Christoph; Merzweiler, Kurt; Lis, Tadeusz; Steinborn, Dirk (Applied organometallic chemistry, 2005)
The platina‐β‐diketone [Pt2{(COMe)2H}2(µ‐Cl)2] (1) was found to react with monodentate phosphines to yield acetyl(chloro)platinum(II) complexes trans‐[Pt(COMe)Cl(PR3)2] (PR3 = PPh3, 2a; P(4‐FC6H4)3, 2b; PMePh2, 2c; PMe2Ph, 2d; P(n‐Bu)3, 2e; P(o‐tol)3, 2f; P(m‐tol)3, 2g; P(p‐tol)3, 2h). In the reaction with P(o‐tol)3 the methyl(carbonyl)platinum(II) complex [Pt(Me)Cl(CO){P(o‐tol)3}] (3a) was found to be an intermediate. On the other hand, treating 1 with P(C6F5)3 led to the formation of [Pt(Me)Cl(CO){P(C6F5)3}] (3b), even in excess of the phosphine. Phosphine ligands with a lower donor capability in complexes 2 and the arsine ligand in trans‐[Pt(COMe)Cl(AsPh3)2] (2i) proved to be subject to substitution by stronger donating phosphine ligands, thus forming complexes trans‐[Pt(COMe)Cl(L)L′] (L/L′ = AsPh3/PPh3, 4a; PPh3/P(n‐Bu)3, 4b) and cis‐[Pt(COMe)Cl(dppe)] (4c). Furthermore, in boiling benzene, complexes 2a–2c and 2i underwent decarbonylation yielding quantitatively methyl(chloro)platinum(II) complexes trans‐[Pt(Me)Cl(L)2] (L = PPh3, 5a; P(4‐FC6H4)3, 5b; PMePh2, 5c; AsPh3, 5d). The identities of all complexes were confirmed by 1H, 13C and 31P NMR spectroscopy. Single‐crystal X‐ray diffraction analyses of 2a·2CHCl3, 2f and 5b showed that the platinum atom is square‐planar coordinated by two phosphine ligands (PPh3, 2a; P(o‐tol)3, 2f; P(4F‐C6H4)3, 5b) in mutual trans position as well as by an acetyl ligand (2a, 2f) and a methyl ligand (5b), respectively, trans to a chloro ligand. Single‐crystal X‐ray diffraction analysis of 3b exhibited a square‐planar platinum complex with the two π‐acceptor ligands CO and P(C6F5)3 in mutual cis position (configuration index: SP‐4‐3). Copyright © 2005 John Wiley & Sons, Ltd. Starting from the platina‐β‐diketone 1 (being easily accessible from hexachloroplatinic acid and Me3SiCCSiMe3), acetylchlorobis(phosphine)platinum(II) complexes 2 with a wide variety of phosphine ligands L are available. Furthermore, ligand substitution reactions of complexes 2 and their decarbonylation to yield methylplatinum complexes are described.